Some Physiological and Immunological Response of Rats (Rattus rattus) to Purified Microcrystal-LR - Moayed Jassim Yass Al-Amari (Journal of Global Pharma Technology, 2017)
The results of present study showed purification of microcrystal-LR from Anabaena circinalis by preparative high performance liquid  chromatography  and observation of some physiological and immunological response of rats to purified microcrystal-LR , the rats was intraperitoneally inject by purified microcrystal-LR from A. circinalis with dose (3, 6, 9) µg/200 gb.w per day for 30 day, the result shown the physiological parameter such as Urea concentration, cholesterol and melatonin concentration in blood and liver tissue were significantly increased with dose elevation of microcrystal-LR as compared with control group, While the total protein concentration in blood and liver tissue was significantly decreased with increasing dose of toxin. The immunological parameter such as interleukin-6 and interleukin-7 in blood and liver tissue were significantly decreased with increasing dose of microcrystal-LR.Keywords: Purified microcrystal-LR, Physiological, Immunological parameter, Cyan toxins.